2021
DOI: 10.4081/jphr.2021.2403
|View full text |Cite
|
Sign up to set email alerts
|

The Socio-Demographic Factors Correlated with Financial Toxicity among Patients with Breast Cancer in Indonesia

Abstract: Background: Breast cancer is one of the major cancer types found among Indonesian women. This cancer diagnosis and its treatment causes perpetual financial burden for the women and their family. This study aims to identify the correlation between socio-demographics with financial toxicity among women with breast cancer in Indonesia.Design and methods: This study design was cross-sectional with 109 respondents of Indonesian breast cancer survivors who were recruited using consecutive sampling. Quantitative data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
0
11
1
Order By: Relevance
“…The patients in this study registered a median COST score of 18, more than 80% of patients with cancer reported at least moderate FT (COST score <26 [ 11 ]), and nearly one-third of them suffered from severe FT (COST score <14 [ 11 ]), lower than the 25.5 and 22.5 reported by other Chinese scholars [ 19 , 25 ]. Although previous studies focused on patients in a single center and with a single disease type, they also demonstrated very serious FT experienced by patients with cancer in China, and the incidence of FT was found to be higher than that of other developing countries [ 10 , 26 , 27 ]. Other related studies have found that characteristics such as rural residents [ 28 ], female [ 29 ], younger age [ 7 , 19 ], unemployment [ 4 , 11 ], marriage [ 27 , 30 ], lower educational level [ 11 , 31 ], and lower income [ 4 , 10 , 19 , 30 ] were associated with higher FT, but our results revealed that FT was independent of gender [ 31 ], marital status [ 26 ], and education [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The patients in this study registered a median COST score of 18, more than 80% of patients with cancer reported at least moderate FT (COST score <26 [ 11 ]), and nearly one-third of them suffered from severe FT (COST score <14 [ 11 ]), lower than the 25.5 and 22.5 reported by other Chinese scholars [ 19 , 25 ]. Although previous studies focused on patients in a single center and with a single disease type, they also demonstrated very serious FT experienced by patients with cancer in China, and the incidence of FT was found to be higher than that of other developing countries [ 10 , 26 , 27 ]. Other related studies have found that characteristics such as rural residents [ 28 ], female [ 29 ], younger age [ 7 , 19 ], unemployment [ 4 , 11 ], marriage [ 27 , 30 ], lower educational level [ 11 , 31 ], and lower income [ 4 , 10 , 19 , 30 ] were associated with higher FT, but our results revealed that FT was independent of gender [ 31 ], marital status [ 26 ], and education [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies focused on patients in a single center and with a single disease type, they also demonstrated very serious FT experienced by patients with cancer in China, and the incidence of FT was found to be higher than that of other developing countries [ 10 , 26 , 27 ]. Other related studies have found that characteristics such as rural residents [ 28 ], female [ 29 ], younger age [ 7 , 19 ], unemployment [ 4 , 11 ], marriage [ 27 , 30 ], lower educational level [ 11 , 31 ], and lower income [ 4 , 10 , 19 , 30 ] were associated with higher FT, but our results revealed that FT was independent of gender [ 31 ], marital status [ 26 ], and education [ 17 ]. Sociodemographic differences in FT were reflected in household residence type [ 27 ], medical insurance policies [ 4 , 7 , 32 ], and OOP medication expenditures which are consistent with existing studies, confirming that demographic risk factors are extensive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Breast cancer is one of the major health burdens in Indonesia. The burdens are different exposures to risk factors, economic settings, lifestyles, access to care and screening, 5 delay in seeking help and non-adherence 6 , financial toxicity, 7,8 , and Social Insurance Administration Organization reported that from 1,308,061 inpatient cancer cases treated in 2016, a total of 2.2 trillion rupiahs was spent, amounting to $486,960,633 in the US dollars (purchasing power…”
Section: Introductionmentioning
confidence: 99%